An auto-correction laser photoacoustic spectrometer based on 2f/1f wavelength modulation spectroscopy. Issue 4 (24th December 2019) - Chen, Ke; Liu, Shuai; Mei, Liang; Jin, Feng; Zhang, Bo; Ma, Fengxiang; Chen, Yewei; Deng, Hong; Guo, Min; Yu, Qingxu
Abstract : An auto-correction laser photoacoustic (PA) spectrometer based on 2 f /1 f wavelength modulation spectroscopy (WMS) has been proposed and demonstrated for trace gas detection to eliminate concentration measurement errors due to light power variations. Abstract : An auto-correction laser photoacoustic (PA) spectrometer based on 2 f /1 f wavelength modulation spectroscopy (WMS) has been proposed and demonstrated for trace gas detection to eliminate concentration measurement errors due to light power variations. A 1.53 μm distributed feedback (DFB) laser is used as a light source to excite the 2 f PA signal that is generated by gas absorption. Meanwhile, a multilayer graphene sheet is employed as a highly efficient photothermal conversion unit for adding a 1 f PA background signal, whose amplitude at the absorption center of the traditional PAS system is almost zero. The experimental results show that the gas concentration measured from the 2 f /1 f WMS signal is almost independent of the laser power. A detection limit of 416 ppb has been achieved for the 1 s measurement interval and could be further improved to 65 ppb with 100 s averaging, according to the Allan deviation analysis.